Pengurangan Lead Time pada Pelayanan End-to-End Logistik melalui Analisis Value Stream Mapping pada PT. X - Arnetta Milenia Tansta; I Gede Agus Widyadana (Jurnal Titra, 2022)
Speed, punctuality and service excellence are a part of the customer orientation value at PT. X. The process of container shipping at PT. X is still considered to have a lengthy lead time, and thus to bring the customer orientation value into reality, PT. X wants to reduce the current lead time and continuously improve customer satisfaction through their services. The research focuses on the selected activities with largest difference between process time and lead time, namely making delivery orders, stuffing and stripping. The result shows that the biggest wastes that occur in the process are defect and waiting. The research is conducted through mapping the whole activities involved in container shipping on current state value stream map, then followed by waste identification and root cause analysis based on the concept of seven wastes and five whys analysis.